Effect of Cetyle Trimethyl Ammonium Bromide (CTAB) surfactant on nanofiltration membrane for dye removal - Abdul Rahman, Hassan; Mohd Khairul Amri, Kamarudin; Hafizan, Juahir; Nurul Hannan, Mohd Safari; Sabariah, Rozali (2017)
Nanofiltration membranes technology commonly used for wastewater treatment especially wastewater containing charged and/or uncharged species. Commonly, textile wastewater possesses high chemical oxygen demand (COD) and non-biodegradable compounds such as pigments and dyes which lead to environmental hazard and serious health problem. Therefore, the objective of this study was to investigate the effects of hydrophilic surfactant on the preparation and performance of Active Nanofiltration (ANF) membrane. The polymeric ANF membranes were prepared via dry/wet phase inversion technique by immersion precipitation process. The Cetyletrimethylammonium bromide (CTAB) as cationic surfactant was added in casting solution at concentrations from 0 to 2.5 wt%. The synthesized membrane performance was evaluated in terms of pure water permeation (PWP) and dye rejection. The experimental data showed that the membrane demonstrated good increment of PWP ranging from 0.27 to 10.28 L/m2 h at applied pressure from 100 to 500kPa, respectively. Meanwhile, the ANF membranes achieved high removal of Methyl Blue and Reactive Black 5 dye up to 99.5% and 91.6%, respectively.